Correlation Between Shoulder Pain Severity, Acromion Morphology, and Acromiohumeral Distance Using MRI: A Study at Haji Adam Malik Hospital Medan in 2022 - Albar, Husnul Fuad; Rendy, Geon; Nanto, Iman Dwi (Universitas Airlangga, 2024)
Background: Studies have shown that rotator cuff tears (RCTs) are the most common cause of shoulder pain and restricted movement. The acromion is a posterior shoulder landmark. Specific acromion morphologies may predispose individuals to rotator cuff tears. Furthermore, studies have found a correlation between supraspinatus tendon tears and acromiohumeral distance. This study examines how shoulder pain assessed with American Shoulder and Elbow Surgeons (ASES) score relates to acromion morphology and acromiohumeral distance on MRI at Haji Adam Malik Hospital in 2022.Methods: This descriptive analytical study employed a cross-sectional approach. A total of 38 patients with a confirmed diagnosis of shoulder pain underwent shoulder MRI examinations and were assessed using the ASES score. Statistical analysis included assessing data normality and performing Spearman correlation analysis. Data were processed and analyzed using SPSS version 25.0.Results: In this study of 38 patients, most participants were women with an average age of 54.66 years. The most common acromion type was type 1 (flat), and the most frequent acromiohumeral distance category was normal. There was no correlation between acromion type and ASES scores, but a moderate correlation was found between the scores and acromiohumeral distance (p=0.016). A positive correlation was observed between type III acromion and ASES score. Conclusion: Shoulder pain based on ASES score has a moderate correlation with acromiohumeral distance and acromion type III variation has a positive correlation although there is no significant correlation was found between shoulder pain and acromion type.